Analysis of 3D multi‐layer microfluidic gradient generator. Issue 2 (23rd November 2016) - Ha, Jang Ho; Kim, Tae Hyeon; Lee, Jong Min; Ahrberg, Christian D.; Chung, Bong Geun
Abstract : We developed a three‐dimensional (3D) simple multi‐layer microfluidic gradient generator to create molecular gradients on the centimeter scale with a wide range of flow rates. To create the concentration gradients, a main channel (MC) was orthogonally intersected with vertical side microchannel (SC) in a 3D multi‐layer microfluidic device. Through sequential dilution from the SC, a spatial gradient was generated in the MC. Two theoretical models were created to assist in the design of the 3D multi‐layer microfluidic gradient generator and to compare its performance against a two‐dimensional equivalent. A first mass balance model was used to predict the steady‐state concentrations reached, while a second computational fluid dynamic model was employed to predict spatial development of the gradient by considering convective as well as diffusive mass transport. Furthermore, the theoretical simulations were verified through experiments to create molecular gradients in a 3D multi‐layer microfluidic gradient generator.